A new species of Pontocrates Boeck, 1871 (Crustacea, Amphipoda, Oedicerotidae) from Cyprus - Gómez, Sergio C. Garcia; Myers, Alan A.; Avramidi, Eleni; Grammatiki, Kleopatra; Lymperaki, Myrsini M.; Resaikos, Vasilis; Papatheodoulou, Magdalene; Louca, Vasilis; Xevgenos, Dimitrios; Küpper, Frithjof C. (Zootaxa, 2024)
A new species of the amphipod genus Pontocrates (Boeck 1871), family Oedicerotidae, is described from Cyprus in the south-eastern Mediterranean Sea. It is a sister taxon to Pontocrates moorei (Myers & Ashelby 2022), currently recorded solely from the British Isles. It is the third species of Pontocrates now known to occur in the Mediterranean Sea.